Monte Carlo dosimetry of a realistic multicellular model of follicular lymphoma in a context of radioimmunotherapy. Issue 10 (18th August 2020) - Bordes, Julien; Incerti, Sébastien; Mora‐Ramirez, Erick; Tranel, Jonathan; Rossi, Cédric; Bezombes, Christine; Bordenave, Julie; Bardiès, Manuel; Brown, Richard; Bordage, Marie‐Claude
Abstract : Purpose: Small‐scale dosimetry studies generally consider an artificial environment where the tumors are spherical and the radionuclides are homogeneously biodistributed. However, tumor shapes are irregular and radiopharmaceutical biodistributions are heterogeneous, impacting the energy deposition in targeted radionuclide therapy. To bring realism, we developed a dosimetric methodology based on a three‐dimensional in vitro model of follicular lymphoma incubated with rituximab, an anti‐CD20 monoclonal antibody used in the treatment of non‐Hodgkin lymphomas, which might be combined with a radionuclide. The effects of the realistic geometry and biodistribution on the absorbed dose were highlighted by comparison with literature data. Additionally, to illustrate the possibilities of this methodology, the effect of different radionuclides on the absorbed dose distribution delivered to the in vitro tumor were compared. Methods: The starting point was a model named multicellular aggregates of lymphoma cells (MALC). Three MALCs of different dimensions and their rituximab biodistribution were considered. Geometry, antibody location and concentration were extracted from selective plane illumination microscopy. Assuming antibody radiolabeling with Auger electron ( 125 I and 111 In) and β − particle emitters ( 177 Lu, 131 I and 90 Y), we simulated energy deposition in MALCs using two Monte Carlo codes: Geant4‐DNA with "CPA100" physics models for Auger electron emitters and Geant4 with "Livermore" physics models for β − particle emitters. Results: MALCs had ellipsoid‐like shapes with major radii, r, of 0.25, 0.5 and 1.3 mm. Rituximab was concentrated in the periphery of the MALCs. The absorbed doses delivered by 177 Lu, 131 I and 90 Y in MALCs were compared with literature data for spheres with two types of homogeneous biodistributions (on the surface or throughout the volume). Compared to the MALCs, the mean absorbed doses delivered in spheres with surface biodistributions were between 18% and 38% lower, while with volume biodistribution they were between 15% and 29% higher. Regarding the radionuclides comparison, the relationship between MALC dimensions, rituximab biodistribution and energy released per decay impacted the absorbed doses. Despite releasing less energy, 125 I delivered a greater absorbed dose per decay than 111 In in the r 0.25 mm MALC (6.78·10 −2 vs 6.26·10 −2 µGy·Bq −1 ·s −1 ). Similarly, the absorbed doses per decay in the r 0.5 mm MALC for 177 Lu (2.41·10 −2 µGy·Bq −1 ·s −1 ) and 131 I (2.46·10 −2 µGy·Bq −1 ·s −1 ) are higher than for 90 Y (1.98·10 −2 µGy·Bq −1 ·s −1 ). Furthermore, radionuclides releasing more energy per decay delivered absorbed dose more uniformly through the MALCs. Finally, when considering the radiopharmaceutical effective half‐life, due to the biological half‐life of rituximab being best matched by the physical half‐life of 177 Lu and 131 I compared to 90 Y, the first two radionuclides delivered higher absorbed doses. Conclusion: In the simulated configurations, β − emitters delivered higher and more uniform absorbed dose than Auger electron emitters. When considering radiopharmaceutical half‐lives, 177 Lu and 131 I delivered absorbed doses higher than 90 Y. In view of real irradiation of MALCs, such a work may be useful to select suited radionuclides and to help explain the biological effects.